Spiritual anti-elitism: Ibn Taymiyya's doctrine of sainthood (walāya) - Sarrió Cucarella, Diego R. (Islam and Christian-Muslim relations, 2011)
The article focuses on Ibn Taymiyya's concept of walāya, the Sufi technical term for sainthood or friendship with God, as exposed in his treatise Al-furqān bayna awliyāʾ al-Raḥmān wa-awliyāʾ al-Shayṭān, The criterion [for distinguishing] between the friends of the All Merciful and the friends of Satan'. A close reading of this text helps us to see that, notwithstanding his criticisms, Ibn Taymiyya did not reject the Sufi tradition wholesale, but tried to bring it within the strict limits of Islamic orthodoxy as he understood it. More specifically, Ibn Taymiyya sought to defend an ideal of walāya within the reach of ordinary Muslims, against what he perceived as the elitism of certain Sufi views of sanctity and the extravagant behavior of marginal holy men. Some of the questions addressed in this work include the major theological issues that Muslim authors had raised with regard to Sufi claims, such as the relationship between prophethood and sainthood, the special qualities of God's friends, and the evidentiary value of saintly miracles.